Design-for-testability for embedded delay-locked loops. - Egan, T.
This paper introduces a new approach to testing a basic analog-only delay-locked loop (DLL) that is embedded in a field-programmable gate array, an application specific integrated circuit, or a system-on-chip (SoC). Part of the DLL circuitry is duplicated and then connected to the DLL in a way that produces a replica of the control voltage. This shadow of the control voltage is used to measure the loop's response to a step in phase. The concept of test construct (TC) gain is introduced as a means of improving detectability. The benefit of the testing approach is demonstrated by injecting defects into the DLL and detecting them through the TC at the observation point.
Keywords: DLL; SoC; TC; Application specific integrated circuit; Control voltage; Delay locked loops; Design for testability; Field-programmable gate array; Step response; System-on-chip.; Test construct